African religions and philosophy - John S. Mbiti (Portsmouth Heinemann Educational Books Inc, 1990)
African Religions and Philosophy is a systematic study of the attitudes of mind and belief that have evolved in the many societies of Africa.
Keywords: Africa, Sub-Saharan -- Religion. Philosophy, African. Religion. Sub-Saharan Africa. Godsdiensten. Filosofie. Religions Africa